2019
DOI: 10.3892/etm.2019.7780
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible electroporation ablation of end‑stage metastatic retroperitoneal lesions: Report on three cases and literature review

Abstract: Metastatic retroperitoneal tumors constitute an end-stage disease with poor prognosis that represents a heavy global health burden. The present study aimed to explore the efficacy of irreversible electroporation ablation (IRE) therapy in patients with end-stage retroperitoneal tumors. Between April 2016 and September 2017, three patients with unresectable retroperitoneal malignant tumors were enrolled. Among these cases, ultrasound (US)-guided IRE was palliatively performed for targeting 3 tumors (1 tumor per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In particular, it has advantages for lesions located in large vessels, the hilar region, bile duct, and ureter (7). Our center previously successfully treated the lesions located in the liver (8), portal vein tumor thrombus (9), and retroperitoneum (10). The follow-up of the patient after IRE showed that the lesions were completely ablated.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has advantages for lesions located in large vessels, the hilar region, bile duct, and ureter (7). Our center previously successfully treated the lesions located in the liver (8), portal vein tumor thrombus (9), and retroperitoneum (10). The follow-up of the patient after IRE showed that the lesions were completely ablated.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition to radiation and contrast sparing, the technique allows continuous imaging throughout the procedure and can confirm the successful ablation zone. 12 CEUS-guided ablation has been used in a multitude of regions, including the liver, 13 kidneys, 14 thyroid, 15 parathyroids, 16 retroperitoneum, 17 uterine fibroids, and abdominal wall endometriosis. 18,19 CEUS has been applied in a range of ablative modalities, including microwave ablation, alcohol ablation, radiofrequency ablation, cryoablation, and irreversible electroporation.…”
Section: Biopsymentioning
confidence: 99%
“…One study on prostate cancer showed comparable efficacy of IRE to standard radical prostatectomy in terms of 5-year recurrence rate, and IRE showed better preservation of urogenital function (76). Two studies found good therapeutic value of IRE in metastatic cancer, including bilateral lung metastasis of osteosarcoma (77) and retroperitoneal metastasis of ovarian, gastric, and pancreatic cancer (78). Another study confirmed that IRE possesses an acceptable safety profile and is effective in eradicating difficultto-reach colorectal liver metastases (CRLMs) (61), while another study showed that IRE is not effective for the treatment of lung malignancies (59).…”
Section: Clinical Efficacy Of Ire On Tumorsmentioning
confidence: 99%